1984
DOI: 10.1287/trsc.18.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Network Design and Transportation Planning: Models and Algorithms

Abstract: Please scroll down for article-it is on subsequent pages With 12,500 members from nearly 90 countries, INFORMS is the largest international association of operations research (O.R.) and analytics professionals and students. INFORMS provides unique networking and learning opportunities for individual professionals, and organizations of all types and sizes, to better understand and use O.R. and analytics tools and methods to transform strategic visions and achieve better outcomes. For more information on INFORMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
473
0
5

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,062 publications
(480 citation statements)
references
References 82 publications
2
473
0
5
Order By: Relevance
“…A model formulation which is capable of representing individual players' decisions is the set up as a Mixed Complementarity Problem (MCP). This setting allows to represent network equilibriums of supply and demand which are more appropriate in models where individual users share the same network (Magnanti and Wong 1984). In this case the individual companies facing carbon policies will potentially share a common CO 2 transport infrastructure.…”
Section: Literature Overviewmentioning
confidence: 99%
“…A model formulation which is capable of representing individual players' decisions is the set up as a Mixed Complementarity Problem (MCP). This setting allows to represent network equilibriums of supply and demand which are more appropriate in models where individual users share the same network (Magnanti and Wong 1984). In this case the individual companies facing carbon policies will potentially share a common CO 2 transport infrastructure.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The fixed charge network design model, which is a fundamental discrete choice design model, is useful for a variety of applications in transportation, distribution, communication, and several other problem settings that make basic cost tradeoffs between operating costs and fixed costs for providing network facilities (see Magnanti and Wong (1984)). The fixed charge design model is deceptively simple.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is to select a subset of arcs that minimizes the sum of the flow (or routing) costs and fixed charge costs. Magnanti and Wong (1984) have shown that the basic fixed charge design model is quite flexible and contains a number of well-known network optimization problems as special cases including the shortest path, minimum spanning tree, uncapacitated plant location, Steiner network, and traveling salesman problems.…”
Section: Introductionmentioning
confidence: 99%
“…Then we define that π k d(k) will always be equal zero. Assuming that constraints (24), (28) and (29) are satisfied, it is easy to see that constraints (25) are equivalent to Bellman's optimality conditions for |K| pairs (o(k), d(k)).…”
Section: One-level Formulationmentioning
confidence: 99%